CYBER-GROOMING IN THE JAPANESE PENAL CODE - Sakai, Tomoyuki (Hitotsubashi journal of law & politics, 2025)
In accordance with Article 182 (1), the act of requesting to meet with a person under 16 years of age by unfair means for the purpose of indecency is a criminal offense. [...]an actual meeting that follows the request to meet shall be subject to more severe penalties (Article 182 (2)). A request to meet by these methods may "distort a young person's decision of whether to meet."'· Nevertheless, the fact does not indicate an objective risk of this resulting in sexual crime at the meeting in question. [...]the risk of sexual crime being committed through a meeting is solely supported by the subjective element of "the purpose of indecency." According to a member of the subcommittee's secretariat, this phrase broadly refers to the purpose of engaging in any acts of sexual significance." [...]a meeting with a person under 16 years of the age does not constitute this crime unless the offender requests to meet through any of acts in items in Article 182 (1). [...]the aforementioned crime would not be constituted in the following cases16: (Case 1) A becomes friend with B (under 16 years of age) on social media and obtains the information from В, such as B's address and the school B attends.